Mapping the Components of the Lebakmuncang Village Tourism Website as an Electronic Promotion Media (E-Tourism): Pemetaan Komponen Website Desa Wisata Lebakmuncang Sebagai Media Promosi Elektronik (E-Tourism) - Verza Aldirindra Nugraha; Medina, Fadita Dwi; Malihah, Elly (Institut Pariwisata dan Bisnis Internasional, 2024)
This study reviews the crucial role of the internet and website as promotional tools for Lebakmuncang Village Tourism in developing tourism potential. The analysis of the website components includes the domain name, creation year, functionality, credibility, and content quality. This mapping aims to improve and develop the website to become an effective promotional medium in accordance with tourism standards. The study also covers promotional activities for Lebakmuncang Village Tourism that rely on internet strategies. However, the use of digital publication remains suboptimal, making the presence of the official website vital for information dissemination. The mapping findings reveal limitations, such as the lack of foreign language content and the use of inappropriate colors. Therefore, optimizing the Lebakmuncang Village Tourism website is necessary to enhance accessibility and appeal to both local and international tourists.